Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis: Updates and Pharmacological Associations (Research, Society and Development, 2024)
Introduction: The use of medications can lead to adverse reactions, including cutaneous manifestations of varying degrees. When these manifestations are severe, a spectrum of conditions including Stevens-Johnson Syndrome (SJS) and toxic epidermal necrolysis (TEN) occurs, characterized by an exacerbated hypersensitivity reaction with subsequent apoptosis of skin keratinocytes. The aim of this study is to elucidate the association with drugs and the clinical aspects and management of these conditions. Methodology: This is an integrative review on the pharmacological associations with SJS/TEN. Data from the Virtual Health Library (BVS), Scientific Electronic Library of Medicine (SciELO), and National Library of Medicine (PubMed) were used, by crossing the descriptors "Stevens-Johnson Syndrome", "antibiotics", "anticonvulsants" and "adverse effects" to answer the question formulated through the PICO strategy. Results and Discussion: Among the drugs associated with the development of SJS/TEN, antibiotics, anti-inflammatory drugs, antiretrovirals, and anticonvulsants stand out, especially sulfonamides and penicillins from the antimicrobial group and aromatic antiepileptics. It is still unclear whether the manifestations differ depending on the causative drug. Diagnosis is usually clinical, aided by the patient's history. Tools can assist in defining management and estimating prognosis. Treatment consists of supportive care and possible pharmacological options, such as the use of cyclosporines. Conclusion: Since this is a rare and potentially fatal condition, more studies are needed to define more effective protocols for management and treatment of patients with SJS/TEN.